Genomic relatedness of a canine Lactococcus garvieae to human, animal and environmental isolates. (July 2021) - Thiry, Damien; Billen, Frédéric; Boyen, Filip; Duprez, Jean-Noël; Quenault, Hélène; Touzain, Fabrice; Blanchard, Yannick; Clercx, Cécile; Mainil, Jacques G.
Abstract: Lactococcus (L.) garvieae is a zoonotic fish pathogen that can also cause bacteraemia and endocarditis in humans and has been isolated from healthy or diseased domestic animals. Nevertheless L. garvieae is more an opportunistic, than a primary pathogen since most affected humans have predisposing conditions and comorbidities. L. garvieae is also present in other animal species, most frequently cattle, but also sheep, goats, water buffaloes, and pigs, and much more rarely dogs, cats, horses, camel, turtle, snake and crocodile. The purpose of this study was to genomically (i) confirm the identification by MALDI-TOF MS® of a L. garvieae from the nasal discharge of a dog with chronic respiratory disorders and (ii) compare this canine isolate with human and animal L. garvieae isolates. According to the BLAST analysis after Whole Genome Sequencing, this canine isolate was more than 99% identical to 3 L. garvieae and belonged to a new Multi-Locus Sequence Type (ST45). MLST and whole genomes-based phylogenetic analysis were performed on the canine isolate and the 40 genomes available in Genbank. The canine L. garvieae was most closely related to an Australian camel and an Indian fish L. garvieae and more distantly to human L. garvieae . Twenty-five of the 29 putative virulence-associated genes searched for were detected, but not the 16 capsule-encoding genes. The heterogeneity of the L. garvieae species is reflected by the diversity of the MLSTypes and virulotypes identified and by the phylogenetic analysis. Highlights: First canine L. garvieae to be genomically analyzed. This canine isolate belong to a new Multi-Locus Sequence Type: ST45. Twenty-five of the 29 putative virulence-associated genes searched for were detected in this canine isolate. Heterogeneity of the L. garvieae species is reflected by the diversity of the MLSTypes and virulotypes.